2018
DOI: 10.1002/dmrr.2992
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from the 1‐hour post‐load glucose level during OGTT: Current screening recommendations for dysglycaemia should be revised

Abstract: This perspective covers a novel area of research describing the inadequacies of current approaches for diagnosing dysglycaemia and proposes that the 1-hour post-load glucose level during the 75-g oral glucose tolerance test may serve as a novel biomarker to detect dysglycaemia earlier than currently recommended screening criteria for glucose disorders. Considerable evidence suggests that a 1-hour post-load plasma glucose value ≥155 mg/dl (8.6 mmol/L) may identify individuals with reduced β-cell function prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 74 publications
1
29
0
Order By: Relevance
“…7 Compared with the rest of the cohort, those youths showed a less favourable clinical and metabolic phenotype, characterized by increased age-and sex-adjusted BMI, a less favourable lipid In this context, 1hPG has been proposed recently as an earlier, more sensitive and accurate predictor of prediabetes and diabetes than currently used biomarkers. 10 While several longitudinal studies have confirmed the ability of 1hPG to predict diabetes and its micro-and macrovascular complications in adults, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]26 there is only a single longitudinal study available in the paediatric population. 27 Our results extend the findings of that study, in that we analysed data from a larger and more heterogeneous cohort of youths, and we used a lower cut point to identify 1-hour hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Compared with the rest of the cohort, those youths showed a less favourable clinical and metabolic phenotype, characterized by increased age-and sex-adjusted BMI, a less favourable lipid In this context, 1hPG has been proposed recently as an earlier, more sensitive and accurate predictor of prediabetes and diabetes than currently used biomarkers. 10 While several longitudinal studies have confirmed the ability of 1hPG to predict diabetes and its micro-and macrovascular complications in adults, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]26 there is only a single longitudinal study available in the paediatric population. 27 Our results extend the findings of that study, in that we analysed data from a larger and more heterogeneous cohort of youths, and we used a lower cut point to identify 1-hour hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, several longitudinal studies have recently identified 1‐hour post‐load glucose concentration (1hPG) during an oral glucose tolerance test (OGTT) as an earlier and more accurate predictor of diabetes than currently used biomarkers . In 2007, Abdul‐Ghani et al found that the area under the ROC curve for 1hPG to predict future diabetes is significantly greater than that of fasting and 2‐hour plasma glucose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify high‐risk individuals with subtle glucose abnormalities earlier when improvement in β‐cell function is more probable with intervention, novel biomarkers with higher sensitivity are required. The 1‐hour plasma glucose (1‐hour PG) ≥155 mg/dL (8.6 mmol/L) during the OGTT has been extensively reviewed and found to be more sensitive than HbA1c or glucose criteria in those with normal glucose tolerance (NGT) for predicting progression to type 2 diabetes, microvascular and macrovascular complications, and mortality 19–23 . Considerable epidemiologic evidence derived from different populations strongly suggests that an elevated 1‐hour PG level may be preferred to current screening tests for identifying high‐risk individuals when ß‐cell function is intact.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, such measurements take place at time 0 (fasting) and 2 h after the ingestion of glucose, but more temporal resolution might be required, or other physiological variables measured, depending on how strict clinical criteria are. Moreover, efforts have been made to modify and standardize the temporal resolution and duration of the tests (Bergman et al, 2018). Besides the clinical interpretation of the OGTT and MT values, some model-derived indexes can be obtained, as is the case of the Insulin Sensitivity S I , derived from the very well known Minimal Model (Bergman et al, 1979).…”
Section: Introductionmentioning
confidence: 99%